Sexual Violence: Christian Theological Legacies and Responsibilities - Scarsella, Hilary Jerome (Religion compass, 2019)
Between the sustained focus of popular attention on the Catholic sexual abuse crisis and the current ubiquity of #MeToo and #ChurchToo discourse, it is clear that sexual violence is a problem within western Christianity. This article speaks to Christian theological legacies of complicity with systems of sexual violence. It sketches ethical, intellectual, and practical trajectories for scholars and practitioners engaging the Christian tradition today to address sexual violence well.